Synthesis and characterisation of new multi-component compounds containing the non-steroidal anti-inflammatory drugs fenbufen and S(+)-ibuprofen - Fr, sler Hannah (Department of Chemistry, 2025)
Fenbufen and S-(+)-ibuprofen are non-steroidal anti-inflammatory drugs with poor aqueous solubility. In attempts to improve their solubility and bioavailability, crystal engineering techniques were employed to synthesise salts, co-crystals and cyclodextrin inclusion complexes containing these drugs. All newly discovered phases were characterised using single-crystal X-ray diffraction (SCXRD), powder X-ray diffraction (PXRD), hot stage microscopy (HSM), Fourier transform infrared (FT-IR) spectroscopy, differential scanning calorimetry (DSC), thermal gravimetric analysis (TGA) and proton nuclear magnetic resonance (1H NMR) spectroscopy. The synthesis of metal salts of fenbufen containing sodium, potassium, calcium and magnesium ions was attempted. Sodium (Fen-Na+ ) and potassium (Fen-K + ) salts were successfully synthesised and characterised, the former also being successfully characterised by SCXRD. Using Fen-Na+ as a potential ‘guest', the syntheses of inclusion complexes with β-cyclodextrin (BCD) and γ-cyclodextrin (GCD) were attempted. The resulting complexes, BCD∙Fen-Na+ , and GCD∙Fen-Na+ , were successfully synthesised and characterised and were shown to have 1:1 cyclodextrin-salt compositions. Solubility studies of all salts and cyclodextrin inclusion complexes reported in this dissertation were performed in both aqueous and Fasted State Simulated Intestinal Fluid (pH 6.5) media. Phase solubility studies of fenbufen were carried out using hydroxypropyl β-cyclodextrin (HPBCD), randomly methylated β-cyclodextrin (RAMEB), γ-cyclodextrin (GCD) and sulfobutyl ether βcyclodextrin sodium (SBEBCD). RAMEB effected the greatest solubility enhancement of fenbufen by a factor of ~200 at the highest CD concentration employed. Liquid-assisted grinding (LAG) and co-precipitation experiments involving fenbufen and watersoluble coformers resulted in the successful synthesis and full characterisation of an ionic co-crystal consisting of fenbufen and isonicotinamide (FEN-ISN) with 2:3 stoichiometry. Salts of S-(+)-ibuprofen with the antifibrinolytic agents 6-aminocaproic acid [(S-IBU)- (ACA)+ ] and tranexamic acid [(S-IBU)- (TXA)+ ] were successfully synthesised and comprehensively characterised. A second crystalline form of a cyclodextrin inclusion complex between S-IBU and heptakis(2,6-diO-methyl)-β-cyclodextrin (DMB∙S-IBU) was discovered. All new phases, (S-IBU)- (ACA)+ , (S-IBU)- (TXA)+ and DMB∙S-IBU, were found to occur with 1:1 stoichiometry.